Fire decreases near‐surface hydraulic conductivity and macropore flow in blanket peat - Holden, Joseph; Wearing, Catherine; Palmer, Sheila; Jackson, Benjamin; Johnston, Kerrylyn; Brown, Lee E (Hydrological processes, 2014)
Many peatlands have been subjected to wildfire or prescribed burning, but it is not known how these fires influence near‐surface hydrological processes. Macropores are important flowpaths in the upper layers of blanket peat and were investigated through the use of tension disc infiltrometers, which also provide data on saturated hydraulic conductivity. Measurements were performed on unburnt peat (U), where prescribed burning had taken place 2 years (B2), 4 years (B4) and >15 (B15+) years prior to sampling, and where a wildfire (W) had taken place 4 months prior to sampling. Where there had been recent burning (B2, B4 and W), saturated hydraulic conductivity was approximately three times lower than where there was no burning (U) or where burning was last conducted >15 years ago (B15+). Similarly, the contribution of macropore flow to overall infiltration was significantly lower (between 12% and 25% less) in the recently burnt treatments compared to B15+ and U. There were no significant differences in saturated hydraulic conductivity or macropore flow between peat that had been subject to recent wildfire (W) and those that had undergone recent prescribed burning (B2 and B4). The results suggest that fire influences the near‐surface hydrological functioning of peatlands but that recovery in terms of saturated hydraulic conductivity and macropore flow may be possible within two decades if there are no further fires. Copyright © 2013 John Wiley & Sons, Ltd.